2023
DOI: 10.1093/mnras/stad1040
|View full text |Cite
|
Sign up to set email alerts
|

Quasar UV/X-ray relation luminosity distances are shorter than reverberation-measured radius–luminosity relation luminosity distances

Abstract: We use measurements of 59/58 quasars (QSOs), over a redshift range 0.0041 ≤ z ≤ 1.686, to do a comparative study of the radius–luminosity (R − L) and X-ray−UV luminosity (LX − LUV) relations and the implication of these relations for cosmological parameter estimation. By simultaneously determining R − L or LX − LUV relation parameters and cosmological parameters in six different cosmological models, we find that both R − L and LX − LUV relations are standardizable but provide only weak cosmological parameter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 132 publications
1
25
0
Order By: Relevance
“…In Khadka et al (2023), we showed that this is in agreement with the tendency for luminosity distances based on L X -L UV relation data to have a mean value smaller than luminosity distances based on R-L relation data for the same QSOs. The median L X -L UV relation luminosity-distance values, on the other hand, are mostly larger except for the flat and non-flat XCDM models.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In Khadka et al (2023), we showed that this is in agreement with the tendency for luminosity distances based on L X -L UV relation data to have a mean value smaller than luminosity distances based on R-L relation data for the same QSOs. The median L X -L UV relation luminosity-distance values, on the other hand, are mostly larger except for the flat and non-flat XCDM models.…”
Section: Introductionsupporting
confidence: 88%
“…For such a sample, in principle, both L X -L UV and R-L relations should be applicable. To this goal, we provided a sample of 58 X-ray-detected reverberation-mapped Mg II QSOs in Khadka et al (2023), from which we measured both the L X -L UV relation and the R-L relation parameter values that are consistent with values measured using larger samples. The sample was quite limited but we stress that for each of the sources we could determine the luminosity distance from these two methods independently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we have here described only the case of distance moduli for GRBs and the case of luminosities for QSOs to be consistent with the fitting procedure applied in our previous analysis. We prefer to construct the cosmological likelihood for QSOs with the logarithmic luminosities, as these are the quantities intrinsic to the RL relation (see Equation (10)) and also the ones that are commonly used for cosmological analyses in the literature (e.g., Khadka & Ratra 2020aLusso et al 2020;Bargiacchi et al 2022;Colgáin et al 2022a;Li et al 2022;Wang et al 2022;Cao & Ratra 2023;Khadka et al 2023;Lenart et al 2023). Thus, this approach allows an easier and more immediate comparison with results from other studies, without the need for taking into account possible differences in the respective methodologies.…”
Section: The Luminosities For Qsosmentioning
confidence: 99%
“…To this end, the community strives to reduce as much as possible the uncertainties on cosmological parameters and to find probes at intermediate redshifts which can be considered standard candles (Yonetoku et al 2004). Given the current interest of the community in quasars as reliable cosmological tools Dainotti et al 2022a; Bargiacchi et al 2022;Khadka et al 2023;Lenart et al 2023), we focus on the hunt for a gold sample for quasars, as already done for gamma-ray bursts (GRBs; Dainotti et al 2010Dainotti et al ,2013Dainotti et al ,2015Dainotti et al ,2016Dainotti et al ,2020Dainotti et al ,2021bDainotti et al ,2022bDainotti et al ,2022cDainotti et al ,2022dDainotti et al ,2023b. We propose an approach to the use of quasars as standard candles similar to the one done for SNe Ia 25 yr ago, but quasars are observed at much larger distances (up to z = 7.54).…”
Section: Introductionmentioning
confidence: 99%